Basics of Financial Market Functioning - Berdieva Mahfuza (Research Parks Publishers, 2023)
The article, based on the provisions of the civil legislation of the Republic of Uzbekistan, analyzes the features of the legal regulation of the financial market, the main provisions of regulatory legal acts regulating the activities of financial market participants in the Republic of Uzbekistan.